Can Frontal Assessment Battery Discriminate Between Patients with Alzheimer’S and Frontotemporal Dementia? - Garcia-Serrano, A (Oxford University Press, 2025)
Objectives: The Frontal Assessment Battery (FAB) is a widely used tool for assessing executive function. However, its ability to distinguish between Alzheimer’s disease dementia (ADD) and behavioural variant frontotemporal dementia (bvFTD) remains under debate. This study assessed the diagnostic utility of the Chilean version of the FAB (FAB-Ch) in differentiating ADD from bvFTD and used data-driven cluster analysis to explore dysexecutive profiles. Method: A total of 288 participants were recruited: 45 with ADD, 33 with bvFTD, and 208 cognitively unimpaired controls (CU). Mean FAB-Ch total scores were compared across groups. Receiver operating characteristic (ROC) curves evaluated the instrument’s ability to distinguish (i) dementia from no dementia, (ii) ADD from bvFTD, and (iii) executive dysfunction. Hierarchical cluster analysis was conducted to identify executive profiles among dementia patients. Results: FAB-Ch scores were significantly lower in individuals with dementia compared to controls (p < .001). However, there were no significant differences between ADD and bvFTD groups (p = .59). The FAB-Ch showed strong discriminatory power between dementia and controls (AUC = 0.882; sensitivity = 0.731; specificity = 0.885), but poor discrimination between ADD and bvFTD (AUC = 0.465; p = .59). Cluster analysis among patients with dementia revealed three distinct executive profiles corresponding to different levels of cognitive impairment (p < .001). Conclusion: The FAB-Ch effectively differentiates individuals with dementia from cognitively unimpaired controls but does not distinguish between ADD and bvFTD. Nevertheless, it is sensitive to executive dysfunction and can aid in the clinical characterization of dementia severity and heterogeneity. © The Author(s) 2025.
Keywords: Frontal assessment battery; dementia; Alzheimer s disease dementia; Behavioral variant frontotemporal dementia; executive dysfunction